The development of conceptual KPI model based on balanced scorecard measurement method for tacit knowledge of universities’ academic staff - Zainab, Amin; Awanis, Romli; Rahmah, Mokhtar; Mazlina, Abdul Majid (Publishing Technology, 2017)
The academic staffs represent the main knowledge resources in universities. The management and development of academic tacit knowledge, which is acquired through activities such as teaching and research is needed for sustained competitive advantage. However, measuring tacit knowledge of academicians, who are the key individuals in organisations, is difficult due to its intangibility. This may result in problems of identifying and determining the key individuals’ performance. Therefore, this paper proposes the development of a conceptual key performance indicator (KPI) model based on balance scorecard (BSc) approach by measuring the level and performance of tacit knowledge for academic staff in universities. The conceptual KPI model is developed by integrating financial and non-financial measurement indicators. These indicators used in the BSc approach to evaluate the success of a university according to the knowledge resources performance and profits from tacit knowledge.